Agronomic behavior of quinoa genotypes (Chenopodium quinoa Willd) in Peru - Estrada-Zúniga, Rigoberto; Apaza-Mamani , Vidal; Pérez-Ávila , Angel; Altamirano-Pérez, Ana; Neyra-Valdez, Edgar (Ecosistemas y Recursos Agropecuarios, 2022)
Quinoa (Chenopodium quinoa Willd) is consumed worldwide for its nutritional composition. It is important to know the agronomic characteristics that are influenced by edaphic and climatic conditions and to evaluate the agronomic performance of 81 quinoa genotypes from the National Institute of Agrarian Innovation (INIA) planted in four locations of Peru: Cusco, Puno, Ayacucho and Junín, under a randomized complete block experimental design with three replications. The following variables were evaluated: plant height, panicle diameter, panicle length, yield, severity of downy mildew infection (Peronospora farinosa) and Selection Index (SI), during the 2017 and 2018 plantings. The comparison of means was performed using Tukey’s test, in addition, cluster analysis, principal components and Pearson’s correlation were performed and the evaluation of the selection index was applied to identify the adaptation of the genotypes. The results showed that the 2018 planting had the highest yields. Cluster analysis found the formation of three groups, where group three showed the best characteristics in yield, plant eight, diameter and panicle length. Principal component analysis showed positive correlations between plant height, diameter and panicle length variables. More than 45% of the treatments showed a selection index greater than one and 16 genotypes were identified with a low level of severity of downy mildew infection. Cusco and Puno reported the best agronomic performance for the 81 genotypes.